Indonesian consumers' intention to use digital bank services - Neshi, Yuriko; Sugiat, Maria Apsari; Silalahi, Fera Maria (Edelweiss Applied Science and Technology, 2025)
Digital banks offer financial services through mobile apps rather than branches. Despite technological advancements, Indonesians rarely use digital banking. To promote the growth of digital banks, it is necessary to research customer preferences. This study aims to analyze consumer intentions to use digital banks based on the theory of planned behavior. The study examined six Indonesian digital banks founded after 2020. It used 487 responses from 69 million digital bank users. Structural equation modeling (SEM) with partial least squares was employed in this study. The SEM analysis showed that all construct variables significantly and positively affect digital bank intention. The coefficient of determination R² for the purchase intention (PI) construct is 0.703, indicating that 70.3% of the variance in the intention to utilize digital banking can be explained by the constructs of attitude (A), subjective norm (SN), and perceived behavioral control (PBC). A positive consumer attitude toward the product is the main predictor of purchase intention. Moreover, the F-square test results indicate that the path from perceived product value to attitude to purchase intention (PPV-A-PI) is the most significant pathway in the model. Consumer attitudes shaped by product perceptions are paramount in influencing decisions to utilize digital banks.